Temperature-swing adsorption of proteins in water using N-isopropylacrylamide copolymer gel particles - Morisada, Shintaro; Namazuda, Ken-ichiro; Kanda, Haruka; Hirokawa, Yoshitsugu; Nakano, Yshio (Advanced powder technology : the international journal of the Society of Powder Technology, Japan, 2010)
The adsorption and desorption behaviors of bovine serum albumin (BSA) in water for temperature-responsive polymer gel particles have been investigated by the temperature-swing operation between 298 and 313K, where the cationic N-isopropylacrylamide (NIPA) gels copolymerized with vinylbenzyl trimethylammonium chloride (VBTA) or 2-(dimethylamino)ethyl methacrylate (DMAEMA) were used. The NIPA-VBTA and the NIPA-DMAEMA copolymer gels adsorbed BSA while the NIPA homopolymer gel hardly adsorbed BSA, indicating that the copolymer gels adsorb BSA through the electrostatic attraction between the positively charged groups in the gels and the negatively charged BSA. The adsorption amounts for the NIPA-DMAEMA gels were smaller than those for the NIPA-VBTA gels. This may be because almost every VBTA group, which is a quaternary ammonium salt, can be positively charged in water, while only some of the tertiary amine DMAEMA groups are protonated in water. Moreover, it was found that both the copolymer gels with a large mesh size of the polymer network repeatedly adsorbed BSA at 298K and desorbed some of pre-adsorbed BSA at 313K by the temperature-swing operation. This BSA desorption may result from the decrease of the number of the positively charged groups accessible to BSA due to the shrinking of the constituent polymer chains.